Optimization of High-Performance-Concrete properties containing fine recycled aggregates using mixture design modeling - Tounsia Boudina (Gruppo Italiano Frattura, 2021)
This investigation means to predict and modeling the fresh and hardened concrete behavior containing fine aggregates from concrete and brick wastes, for different recycled aggregates substitution rates.